Analysis Of The Effect Of Occupational Safety And Health (Osh) And Work Facilities On Employee Productivity At Bintang Amin Hospital, Bandar Lampung: Analisis Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Dan Fasilitas Kerja Terhadap Produktivitas Karyawan Di Rumah Sakit Bintang Amin Bandar Lampung - Khofifah Sinta Nuria; Kosasih Kosasih; Ayu Laili Rahmiyati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Occupational safety and health as well as workplace facilities are critical elements for establishing a secure and productive operational environment in the healthcare sector. Specific Background: Bintang Amin Hospital in Bandar Lampung operates as a major referral medical facility addressing high-risk hospital tasks. Knowledge Gap: The simultaneous statistical contribution of occupational safety metrics and working facilities to employee output within regional healthcare institutions requires empirical examination. Aims: This study aimed to analyze the effects of occupational safety and health and workplace facilities on employee productivity at Bintang Amin Hospital, Bandar Lampung. Results: Employing a quantitative approach with descriptive and verificative methods through multiple linear regression on 190 respondents, the findings indicated that safety practices, workplace facilities, and productivity averaged high scores of 4.42, 4.43, and 4.30 respectively, with safety standards (t=3.893; p=0.000) and facilities (t=5.253; p=0.000) exerting positive and significant partial effects, while simultaneously accounting for an R2 of 0.380 (F=56.732; p=0.000). Novelty: This research integrates safety protocols and facility infrastructure into an empirical framework for evaluating hospital workforce output dynamics. Implications: Healthcare management must continually sustain and refine occupational safety protocols and facility infrastructure to support enduring employee output and service quality. Highlights Safety practices and workplace facilities at Bintang Amin Hospital predominantly achieve very high average evaluation scores of 4.42 and 4.43. Multiple linear regression establishes that safety protocols and physical amenities simultaneously contribute a 38% variance explanation to employee productivity. Empirical validation confirms that workplace facility provisions demonstrate a robust positive partial t-statistic value of 5.253 regarding staff output. Keywords Occupational Safety And Health (OSH); Work Facilities; Employee Productivity; Hospital Management; Workforce Performance